Aptamer superstructure-based electrochemical biosensor for sensitive detection of ATP in rat brain with in vivo microdialysis. Issue 5 (18th January 2019) - Jiang, Yanan; Ma, Wenjie; Ji, Wenliang; Wei, Huan; Mao, Lanqun
Abstract : An electrochemical biosensor with an aptamer superstructure as the recognition element is demonstrated for highly sensitive detection of ATP in the cerebral system. Abstract : Highly sensitive and selective sensing of ATP in rat brain has attracted increasing interest from interdisciplinary fields of analytical chemistry and neuroscience owing to the importance of ATP in cellular metabolism and signal transduction. Herein, we demonstrated an electrochemical biosensor having an aptamer superstructure as a recognition element for the selective and sensitive detection of ATP in rat brain. Unlike the electrochemical aptamer-based sensors (aptasensors) built by assembling a simple DNA structure containing only one aptamer unit onto the electrode substrate, the aptasensor described here was developed by assembling an aptamer superstructure consisting of consecutive aptamer units in DNA strands onto the electrode substrate. Each aptamer unit in the superstructure was labelled with an electrochemical probe ( i.e., methylene blue, MB) for signal readout. The aptamer superstructure was assembled onto the surface of a gold electrode to form the electrochemical aptasensor. In the presence of ATP, the strong electrochemical signals produced by multiple redox molecules labeled on the aptamer units clearly decreased because of the disassembling of the aptamer superstructure from the electrode surface due to strong interactions between ATP and the aptamer units. In this approach, the aptasensor was well responsive to the ATP concentration, and the current decrease was linearly related to the ATP concentration ranging from 0.1 nM to 1 mM. Moreover, the aptasensor has high selectivity and good regenerability. Due to these properties, the aptasensor with an aptamer superstructure can exhibit practical applications for ATP assay in rat brain combined with in vivo microdialysis.